Hubungan Pola Makan dan Gaya Hidup dengan Terjadinya Obesitas pada Anak Usia 7-12 Tahun di Kavling Flamboyan di Kota Batam Tahun 2021 - Justiyulfah Syah; Desy Desy; Afif D Alba; Zulikha Zulikha (Pusat Riset dan Inovasi Nasional, 2021)
Obesity is a disorder or disease due to an imbalance between energy intake and energy output so that it becomes an excessive accumulation of fat tissue in the body. Several factors that cause obesity include diet, physical activity and a sedentary lifestyle. This study aims to analyze the relationship between diet and lifestyle with the occurrence of obesity in children aged 7-12 years in the flamboyant plot of Batam city in 2021. This study is a descriptive analytic study with a cross sectional design. Respondents in this study 56 respondents. The sampling technique used is direct observation of respondents and using a questionnaire. The results obtained are 75% aged 7-10 years, for gender 100% half of the children are male and female, 67.9% of obese children who have a good diet, 62.5% of children Obese have a pretty lifestyle. Chi-square test results with = 0.05. The results showed that there was a relationship between diet (p = 0.000) and lifestyle (p = 0.000) with obesity. there is a relationship between diet and lifestyle with the occurrence of obesity in children aged 7-12 years in the flamboyant plot of Batam city in 2021. Suggestions to be able to increase efforts in analyzing diet and lifestyle by providing counseling to parents so that children can reduce obesity in children.